Analysis of community needs and wants, and strategies to ensure effective community services in rural areas - Chowdhury, Md. Mahamood Salekin (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.